Survey and Present Status of Soybean Diseases in Central India - Amrate, Pawan K. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during kharif (July to September), 2018 and 2019 at J.N.K.V.V., Jabalpur, Madhya Pradesh, India to study the current status of soybean diseases in central Indian conditions. A fixed plot survey of nine soybean varieties was carried out at three different growth stages i.e. seedling stage (V2-V3), early reproductive stage (R2-R4) and late reproductive stage (R5-R7). The study found that soybean varieties were infected with fourteen diseases in the current cultivation scenario. Collar rot (0.0–4.88%), root rot (0.63–4.13%) and soybean mosaic (0.0–8.38%) was initially noticed at the seedling stage in the second and third week of July. At early reproductive stages, yellow mosaic (0.0–35.0%), bacterial pustule (0.0–8.0%), and anthracnose (0.00–35.13%) were dominating diseases in the third week of July (yellow mosaic) to the first week of August (bacterial pustule). At late reproductive stage (first week of August to the third week of September), the average range of incidence of aerial blight (1.25–30.63%), frog eye leaf spot (0.75–21.13%), charcoal rot (0.0–65.13%), Pod blight (0.0–10.63%), myrothesium leaf spot (0.0–2.88%), target leaf spot (0.0–6.13%) and alternaria leaf spot (0.0–5.0%) were varied from low to high. At maturity, the soybean seeds were infected with purple seed stain (0.38–7.0%). Through incidence and varietal influence patterns, charcoal rot, yellow mosaic, Anthracnose/pod blight, aerial blight, and frog eye leaf spot could be considered significant concerns for soybean cultivation in this region.